Oral squamous cell carcinoma patients which human papilloma virus infection: a case control study in Muwardi Hospital Surakarta, Central Java, Indonesia - ADI PRAYITNO; ELYANA AZNAR; POERNOMO POERNOMO; SUHARTONO TAAT PUTRA (Nusantara Bioscience, 2011)
Abstract. Prayitno A, Aznar E, Poernomo, Putra ST. 2011. Oral squamous cell carcinoma patients which human papillomavirus infection: a case-control study in Muwardi Hospital Surakarta, Central Java, Indonesia. Nusantara Bioscience 3: 64-67. Annual incidence rates for oral and pharyngeal cancer are estimated at 25 cases per 100,000 in developing countries. Human papillomavirus (HPV) was implicated in pathogenesis of Oral Squamous Cell Carcinoma (OSCC). Aims of this research were to know the incidence of OSSC patient which realized HPV infection. Women OSCC (15) and Benign Oral Squamous Cells (BOSC) (40) tissue biopsy frozen sections were from Departement of Oral and Dental, Muwardi Hospital in Surakarta from January to December 2007. Tissue was cut into two parts. To ascertain the type of neoplasm was subsequently stains with HE. To amplify the L1-HPV gene for 450bp long. Chi-Square Test analyzed the collected data. The result of this experiment showed nine patients from 40 patients BOSC identified have HPV infections (9/40 = 23%). Eleven patient from 15 patient OSCC identified have HPV infections (11/15 = 73%). From Chi-Square analysis have significant differences between BOSC and OSCC. HPV is a factor for OSCC pathogenesis.